2012
DOI: 10.1007/s10856-012-4640-4
|View full text |Cite
|
Sign up to set email alerts
|

Injection of calcium phosphate pastes: prediction of injection force and comparison with experiments

Abstract: Calcium phosphate ceramics suspensions (ICPCS) are used in bone and dental surgery as injectable bone substitutes. This ICPCS biomaterial associates biphasic calcium phosphate (BCP) granules with hydroxypropylmethylcellulose (HPMC) polymer. Different ICPCS were prepared and their rheological properties were evaluated in parallel disks geometry as a function of the BCP weight ratio (35, 40, 45 and 50 %). The suspensions show a strongly increased viscosity as compared to the suspending fluid and the high shear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Furthermore, it was demonstrated that the viscosity decreased with increasing shear rate (see Figure 1 B). As expected for a long-chain and unbranched molecule, HPMC in H 2 O was a shear-thinning material, which is consistent with the results of the rheological studies by Fatimi et al [ 22 ]. Increasing entanglement of polymer chains with storage time resulted in an increase in viscosity.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it was demonstrated that the viscosity decreased with increasing shear rate (see Figure 1 B). As expected for a long-chain and unbranched molecule, HPMC in H 2 O was a shear-thinning material, which is consistent with the results of the rheological studies by Fatimi et al [ 22 ]. Increasing entanglement of polymer chains with storage time resulted in an increase in viscosity.…”
Section: Discussionsupporting
confidence: 91%
“…This increases P PS (Eq. 4) and has been demonstrated to reduce [35,79] and even eliminate [76,[80][81][82] [80]. Contrastingly, Wang et al [83] reported that the viscous gel produced with the addition of modified starch to CPC reduced injectability.…”
Section: Viscosity Of Liquid Phasementioning
confidence: 99%
“…11 to obtain key parameters from the rheometry of a CPC (i.e. biphasic CaP and HPMC aqueous solution)[81]. The parameters were used with the Hagan-Poiseuille equation to estimate the extrusion pressure for the CPC.…”
mentioning
confidence: 99%
“…However, Montufar et al did find needle geometry had an effect on the injectability of CPC. Burguera et al [ 16 ] and Fatimi et al [ 42 ] also found needle geometry had a significant effect on the extrusion of CPC, however both studies used a more viscous liquid phase (hydroxypropyl methylcellulose-water solution) and no phase separation was exhibited.…”
Section: Discussionmentioning
confidence: 99%